Visual learning methods: strategy for mitigating unethical decisions in accounting education - Natasia Alinsari; Intiyas Utami; Marwata Marwata (Universitas Hayam Wuruk Perbanas, 2020)
The purpose of this study is to examine the causality between obedience pressures and unethical decisions making and whether the causality can be mitigated by visual-based ethics learning methods. This study employs 2x2 between subjects factorial experiment methods with 114 participants from undergraduate students in accounting. The result of this study shows that there is a causal relationship between obedience pressures and unethical decisions making and that visual-based learning methods have encouraged subjects to make more ethical decisions. In addition, this study also finds that the most ethical decision outcomes are generated by the subjects who are under high obedience pressures and receive visual-based ethics learning methods.